PRODUCTION AND MARKETING BILIH FISH (Mystacoleucus padangensis bleeker) SUB IN VILLAGE NAPITUPULU BALIGE TOBA SAMOSIR NORTH SUMATRA PROVINCE - Butarbutar, Soecipto; Yulinda, Eni; ', Hendrik (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The purpose of this study was to determine the fish production of Bilih in the Napitupulu/year, describing marketing and to know the area of marketing, analyze costs marketing. The method used in this research is survey method.Results of this study is Bilih fish production in Napitupulu during the season many are as much as 330 kg/day. In the season middle is 245 kg/day, whereas during the fishing season does not Bilih fish production is 165 kg/day. So strata Bilih fish production in Napitupulu is 246 kg/day. Products of Bilih fish that there are two types of Bilih fish that are fresh and fried Bilih fish that. The production of Bilih fresh is 98 kg/day for Sibolga marketing, Bilih fried fish production is 49 kg/day with marketing West Sumatra. Income of fishermen who use fishing gear floating chart is Rp 4,827,085/month, fishermen using nets is Rp 514,861/month. The channel of marketing for Bilih fish are: producer/fisherman – traders – Sibolga retailers – consumers Sibolga. The channel of marketing Bilih fried fish are: traders/processors – retailers West Sumatra – consumers of West Sumatra. The highest marketing costs are on traders that is Rp 64,752,779/month with receipt Rp 11,197,221/month. The marketing Bilih fish for West Sumatra Sibolga had efficient.Keywords: Production Bilih fish, the marketing of Bilih fish